Gestational Diabetes During and After Pregnancy - Kim, Catherine; Ferrara, Assiamira; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
Gestational Diabetes Mellitus is becoming an increasingly prevalent disease as obesity and other chronic diseases are on the rise. It requires careful and informed clinical management as the care received during pregnancy affects not only perinatal health but the risk of developing type 2 diabetes even decades into the future, in both the mother and the child.From epidemiology and pathophysiology to diagnosis and management, covering recent breakthroughs in research and up-to-date developments in clinical practice, Gestational Diabetes During and After Pregnancy offers the reader a comprehensive and current look at Gestational Diabetes. Public Health issues are also addressed, with discussions on screening, control programs and policy. Also included are the results of the landmark Hyperglycemia and Adverse Pregnancy Outcome (HAPO) study.Anyone involved in the research, public health or clinical aspects of Gestational Diabetes will find this volume a valuable aid in consolidating all recent developments regarding this disease.
An Overview of Problems and Solutions in the Diagnosis and Treatment of Gestational Diabetes -- SECTION I: SCREENING FOR AND IDENTIFICATION OF GDM DURING PREGNANCY -- Hyperglycemia and Adverse Pregnancy Outcome (HAPO) Study: An Overview -- Evolution of screening and diagnosis criteria for GDM worldwide -- SECTION II: BURDEN OF GDM IN US POPULATIONS -- Prevalence of GDM -- Risk Factors for Gestational Diabetes: From an Epidemiological Standpoint -- SECTION III: BURDEN OF GDM IN DEVELOPING COUNTRIES -- Burden of GDM in Developing Countries -- SECTION IV: PATHOPHYSIOLOGY AND GENETICS OF GDM -- Insulin and the Placenta in GDM -- What causes Gestational Diabetes? -- Mechanisms Underlying Insulin Resistance in Human Pregnancy and Gestational Diabetes Mellitus -- Inflammation, Adipokines, and Gestational Diabetes Mellitus -- Lipids in Gestational Diabetes: Abnormalities and Significance -- Blood Pressure in GDM -- Genetics of Gestational Diabetes Mellitus and Type 2 Diabetes -- SECTION V: COMORBIDITIES OF GDM -- Maternal Obesity and Epidemiological Review of Pregnancy Complications -- Maternal Comorbidities During Gestational Diabetess Mellitus: Obstetrical Complications, Prematurity and Delivery -- The Diabetic Intrauterine Environment: Short and Long-Term Consequences -- SECTION VI: MANAGEMENT OF GDM DURING PREGNANCY -- Exercise Recommendations in Women with Gestational Diabetes Mellitus -- Nutrition and Weight Recommendations for Treating Gestational Diabetes Mellitus -- Pharmacological Treatment Options for Gestational Diabetes -- SECTION VII: POSTPARTUM IMPLICATIONS FOR GDM IN WOMEN -- Risk for Maternal Postpartum Diabetes -- Contraception Before and After GDM -- Lactation and Diabetes Among Women with a History of GDM -- SECTION VIII: GDM INTERVENTIONS -- Emerging Science: Interventions in Women at Risk of GDM During Pregnancy -- Diabetes Prevention Interventions for Women with a History of GDM -- SECTION IX: DIABETES CONTROL PROGRAMS AND POLICY -- Diabetes Control Programs and Policy.
Keywords: Medicine; Gynecology; Obstetrics; Maternal and child health services; Health informatics; Endocrinology; Medicine & Public Health; Endocrinology; Maternal and Child Health; Obstetrics/Perinatology.; Health Informatics; Gynecology; Electronic books